Systemic immunosuppression promotes survival and integration of subretinally implanted human ESC-derived photoreceptor precursors in dogs - Ana Ripolles‐Garcia; Natalia V. Dolgova; M. Joseph Phillips; Svetlana Savina; Allison L. Ludwig; Sara A. Stuedemann; Uchenna Nlebedum; John H. Wolfe; Oliver A. Garden; Arvydas Maminishkis; Juan Amaral; Kapil Bharti; et al. (2022)
Regenerative therapies aimed at replacing photoreceptors are a promising approach for the treatment of otherwise incurable causes of blindness. However, such therapies still face significant hurdles, including the need to improve subretinal delivery and long-term survival rate of transplanted cells, and promote sufficient integration into the host retina. Here, we successfully delivered in vitro-derived human photoreceptor precursor cells (PRPCs; also known as immature photoreceptors) to the subretinal space of seven normal and three rcd1/PDE6B mutant dogs with advanced inherited retinal degeneration. Notably, while these xenografts were rejected in dogs that were not immunosuppressed, transplants in most dogs receiving systemic immunosuppression survived up to 3–5 months postinjection. Moreover, differentiation of donor PRPCs into photoreceptors with synaptic pedicle-like structures that established contact with second-order neurons was enhanced in rcd1/PDE6B mutant dogs. Together, our findings set the stage for evaluating functional vision restoration following photoreceptor replacement in canine models of inherited retinal degeneration.